Shifting and power sharing control of a novel dual input clutchless transmission for electric vehicles. (1st May 2018) - Liang, Jiejunyi; Yang, Haitao; Wu, Jinglai; Zhang, Nong; Walker, Paul D.
Highlights: Development of a multispeed dual input clutchless transmission system. Achieve non-interrupted power-on shifting with the proposed shifting control strategy. A real-time PSC strategy is designed to both improve efficiency and drivability. Simulations demonstrate the effectiveness of proposed system and its control strategies. Abstract: To improve the overall efficiency of electric vehicles and guarantee the driving comfort and vehicle drivability under the concept of simplifying mechanism complexity and minimizing manufacturing cost, this paper proposes a novel clutchless power-shifting transmission system with shifting control strategy and power sharing control strategy. The proposed shifting strategy takes advantage of the transmission architecture to achieve power-on shifting, which greatly improves the driving comfort compared with conventional automated manual transmission, with a bump function based shifting control method. To maximize the overall efficiency, a real-time power sharing control strategy is designed to solve the power distribution problem between the two motors. Detailed mathematical model is built to verify the effectiveness of the proposed methods. The results demonstrate the proposed strategies considerably improve the overall efficiency while achieve non-interrupted power-on shifting and maintain the vehicle jerk during shifting under an acceptable threshold.